Silsesquioxane-based and triptycene-linked nanoporous polymers (STNPs) with a high surface area for CO2 uptake and efficient dye removal applications. Issue 9 (17th November 2020) - Alam, Akhtar; Hassan, Atikur; Bera, Ranajit; Das, Neeladri
Abstract : Nanoporous STNPs obtained by crosslinking octavinylsilsesquioxane and triptycene have superior gas-storage and dye capture abilities than most silsesquioxanes derived adsorbents. Abstract : A unique set of polymers were conveniently obtained by marriage of 'cubic' octavinylsilsesquioxane (OVS) and 'paddle wheel' shaped triptycene using the simple and economical Friedel–Crafts reaction. The resulting 'hybrid inorganic–organic polymers' (STNPs) are nanoporous with higher surface areas than several previously reported porous polymeric networks containing either one of the two structural motifs (OVS or triptycene). In addition, the STNP with the highest surface area (STNP3 ) also has better gas storage and dye capture abilities than several organic adsorbents derived from silsesquioxanes. The performance of STNP3 as a dye adsorbent suggests that it can be further explored for environmental remediation.